2003
DOI: 10.22260/isarc2003/0013
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Snaking Phenomenon to Improve Directional Stability of Remote Controlled Articulated Wheel Tool-Carrier

Abstract: This paper describes tests and trials conducted on 20 tons articulated wheel loader to get answer how the snaking phenomenon is arisen. Used methods, achieved original results and their analysis are presented. It could be basis for future works on articulated tractor directional stabilisation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This study uses the Dugoff tire model, and the tire model is complementary to the elastic basis analysis model developed by Fiala and the lateral force-vertical force synthesis model of Pacejka and Sharp. The tire model provides a method to calculate forces under the combined lateral and longitudinal forces [18]. The most important feature is that it is fast and requires only a few parameters for calculation.…”
Section: Tire Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses the Dugoff tire model, and the tire model is complementary to the elastic basis analysis model developed by Fiala and the lateral force-vertical force synthesis model of Pacejka and Sharp. The tire model provides a method to calculate forces under the combined lateral and longitudinal forces [18]. The most important feature is that it is fast and requires only a few parameters for calculation.…”
Section: Tire Modelsmentioning
confidence: 99%
“…Mu [17] showed that elastic torsional suspension can improve the roll stability of vehicles, but the directional stability at high speed of vehicles with suspension is poorer than that of vehicles without suspension. Lopatka and Muszynski [18] analysed the limited perception of driver, which has insensitivity zones of the lateral and angular locations. Drivers rely heavily on rotational motion and their senses to prevent vehicles from snaking; hence, drivers have a significant impact on vehicle stability.…”
Section: Introductionmentioning
confidence: 99%
“…Conducted at MUT research [6], [7] shows that main reasons of the snacking phenomenon are : -initial turns of articulated frame (below 0,6 0 ), -residual steering moment in hydraulic cylinders. In Ackerman steering system due to suitable geometry there are a few torques and forces that can acts straighten road wheels because of play in steering system and stabilize of vehicle movement [2].…”
Section: Concept Of Stabilizing Systemmentioning
confidence: 99%
“…In Ackerman steering system due to suitable geometry there are a few torques and forces that can acts straighten road wheels because of play in steering system and stabilize of vehicle movement [2]. Different geometry of steering and play absence in articulated tractors cause the stabilising function of steering system is fulfiled by the driver [7]. Their perception limits accurency of vehicle leding, directional stability of movement and top permitable speed.…”
Section: Concept Of Stabilizing Systemmentioning
confidence: 99%
See 1 more Smart Citation